Case Stydy - Choroidal Melanoma in Ocular Melanocytosis - Muhammad Kamran Khalid, Lal Mohammad, Muhammad Tariq Khan, Sanaullah Jan, Zakir Hussain, Samina Karim, (Pakistan Journal of Ophthalmology, 2010)
Ocular melanocytosis is the melanocytic hyperplasia of the deeper layers of cojunctiva or the episclera. This should be differentiated from the other clinical entity, i.e. ocular melanosis, which is defined as melanocytic hyperplasia of the epithelial layers of conjunctiva. Ocular melanocytosis, although rare in white races, is associated with somehow increased risk of uveal malignant melanoma. In darkskinned races, the disease entity is comparatively more common but its association for developing uveal melanomas is extremely rare. We report a case of congenital ocular melanocytosis, later on complicated by choroidal malignant melanoma, in a dark-skinned Pakistani citizen. A 35 years old male with congenital conjunctival melanocytosis of the right eye (left eye being un-affected) presented to us. His visual functions remained unaffected till the age of 33 years, when he noticed slight dimness of vision in his right eye. At the time of presentation, his vision had dropped to light perception in the affected eye. After detailed clinical work up and after performing some necessary investigations, a diagnosis of choroidal malignant melanoma was made. The eye was enucleated and histopathological examination confirmed the diagnosis.